Optimising of resource utilisation at a university - an allocation problem - C.J. Scogings; P.W. Uys (ORiON, 2003)
Student enrolment at the University of Natal has been increasing steadily over the years. Moreover additional new courses are introduced from time to time. Despite this State subsidies are declining in real terms. These factors imply escalating demands on physical resources. Historically, at this university, lecture rooms have been used only during the mornings and laboratories only during the afternoons. An obvious solution to meet the demand for accommodation is to double up on the number of timetabled periods so that the lecture rooms are in use the whole day. Since there are many classes which are in fact too large to be accommodated in any one room it is also necessary to split these classes into separate lecture groups. Likewise classes have to be divided up into several smaller groups for laboratory and tutorial sessions. The policy at this university is to encourage students to choose curricula including courses selected from as wide a range as possible. The above timetable strategy apparently facilitates this. In practice, however, to ensure that student numbers are evenly distributed across alternative sessions for a given course and to do this for all courses simultaneously while avoiding clashes is not a simple matter.